2019
DOI: 10.3390/ma12152430
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization for Compression Molding of Carbon Fiber–Reinforced Thermosetting Polymer

Abstract: To enhance the quality and mechanical performance of a carbon fiber–reinforced polymer (CFRP) workpiece, this paper prepares a polyacrylonitrile (PAN)-based carbon fiber–reinforced thermosetting polymer (CFRTP) laminated board through compression molding, and carries out orthogonal tests and single-factor tests to disclose the effects of different process parameters (i.e., compression temperature, compression pressure, pressure-holding time, and cooling rate) on the mechanical performance of the CFRTP workpiec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In a similar manner, increased temperature along with increased duration of molding reduced the tensile strength despite insignificant linear effect of the later variable (Figure 4b). According to Xie et al (2019), low temperature of compression molding may lead to insufficient impregnation of fillers and adjacent polymer chains while too high a temperature can lead to degradation. Meanwhile, longer duration could beneficially affected tensile strength due to improved resin flow and better fillers impregnation.…”
Section: Effect Of the Compression Molding Variables On The Mechanical Properties Of Uhmwpe/cnf Bio-nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner, increased temperature along with increased duration of molding reduced the tensile strength despite insignificant linear effect of the later variable (Figure 4b). According to Xie et al (2019), low temperature of compression molding may lead to insufficient impregnation of fillers and adjacent polymer chains while too high a temperature can lead to degradation. Meanwhile, longer duration could beneficially affected tensile strength due to improved resin flow and better fillers impregnation.…”
Section: Effect Of the Compression Molding Variables On The Mechanical Properties Of Uhmwpe/cnf Bio-nanocompositesmentioning
confidence: 99%
“…Nevertheless, long duration molding could be a disadvantage, which may expose polymer to degradation (Campo, 2008), especially in consolidation of UHMWPE containing cellulose nanofiber (CNF) fillers. Appropriate compression molding parameters are essentially needed for polymer diffusion and filler impregnation into the matrix (Xie et al, 2019) while avoiding polymer degradation. Meanwhile, in order to improve its productivity, the shorter duration is imperative for more effective processing.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 40:60 (fiber to resin ratio) as the optimum condition to achieve improved performance in terms of tensile, flexural, and impact behavior of the composite. Xie et al 26 fabricated polyacrylonitrile (PAN)/CF‐reinforced thermosetting polymer using a hot compression technique. Results revealed that optimum conditions for improved performance in terms of tensile, bending and interlaminar shear strength were achieved at 150°C compression temperature, 20 min holding time under a pressure of 50 T, 3.5°C/min cooling rate, and 80°C mold‐opening temperature.…”
Section: Introductionmentioning
confidence: 99%
“…e obtained temperature and pressure results were imported into ANSYS, and ANSYS was used to simulate the heating process of the molding and analyze the stress and strain conditions of the molding, but the optimal pressure and temperature combination have not been fully studied; the best molding process parameters cannot be obtained; orthogonal experiments have not been performed; and the data cannot be further verified. Xie et al [3] carried out an orthogonal experiment to analyze the influence of the four process parameters of forming temperature, forming pressure, dwell time, and cooling rate on the performance of the sheet and determined the best forming process parameters, but the effect of heating time on compression molding was not analyzed and the obtained process parameters were not further optimized. Fujihara et al [4] designed and completed orthogonal experiments in order to obtain the optimum forming process parameters of PEEK.…”
Section: Introductionmentioning
confidence: 99%